2020
DOI: 10.1038/s41598-020-58470-0
|View full text |Cite
|
Sign up to set email alerts
|

The Eupentacta fraudatrix transcriptome provides insights into regulation of cell transdifferentiation

Abstract: the holothurian Eupentacta fraudatrix is a unique organism for studying regeneration mechanisms. Moreover, E. fraudatrix can quickly restore parts of its body and entire organ systems, yet at the moment, there is no data on the participation of stem cells in the process. to the contrary, it has been repeatedly confirmed that this process is only due to the transformation of terminally differentiated cells. in this study, we examine changes in gene expression during gut regeneration of the holothurian E. frauda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 70 publications
2
34
1
Order By: Relevance
“…Although there are some differences in the evisceration and regeneration process of this species that might explain the differential gene expression, its regeneration process also involves dedifferentiation of cells within the mesenteric tissue, thus a certain degree of similarity would have been expected. Nonetheless, DETF identified in E. fraudatrix 24 were not found in our study, or if present, their differential expression showed no correlation. Examples of this expression discrepancy: EGR1, TCF24 and SNAI2, upregulated in E. fraudatrix , downregulated in H. glaberrima .…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Although there are some differences in the evisceration and regeneration process of this species that might explain the differential gene expression, its regeneration process also involves dedifferentiation of cells within the mesenteric tissue, thus a certain degree of similarity would have been expected. Nonetheless, DETF identified in E. fraudatrix 24 were not found in our study, or if present, their differential expression showed no correlation. Examples of this expression discrepancy: EGR1, TCF24 and SNAI2, upregulated in E. fraudatrix , downregulated in H. glaberrima .…”
Section: Discussioncontrasting
confidence: 85%
“…Further studies with a broader approach targeted expressed sequence tags (ESTs) from cDNA libraries of regenerating intestines and the preparation of microarrays to reveal DEGs. In the last decade, these technologies have been used to uncover regenerationassociated genes in the transcriptomes of two other sea cucumbers, Apostichopus japonicus 23 and Eupentacta fraudatrix 24 . This has led to the identification of several DEGs linked with intestinal regeneration.…”
mentioning
confidence: 99%
“…S2 online), the number of DETs is similar (3587) to those reported in the A. japonicus study. Our results are also comparable with a study done in E. fraudatrix applying equivalent significance benchmarks (adjusted p-value < 0.05) documenting 17,227 DETs in regenerating intestine relative to intact gut 24 .…”
Section: Discussionsupporting
confidence: 88%
“…Further studies with a broader approach targeted expressed sequence tags (ESTs) from cDNA libraries of regenerating intestines and the preparation of microarrays to reveal DEGs. In the last decade, these technologies have been used to uncover regeneration-associated genes in the transcriptomes of two other sea cucumbers, Apostichopus japonicus 23 and Eupentacta fraudatrix 24 . This has led to the identification of several DEGs linked with intestinal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study in the sea cucumber Eupentacta fraudatrix has identified 11 genes encoding transcription factors that could be associated with transdifferentiation in holothurian intestinal regeneration, although the evidence for this is strictly circumstantial. These factors are involved in distinct cellular process in other organisms and their expression increases during days 5-7 of regeneration when the transformation of coelomic epithelial cells into enterocytes occurs (Boyko et al, 2020).…”
Section: Selected Relevant Functional Gene Groupsmentioning
confidence: 99%